Gene action controlling normalized difference vegetation index in crosses of elite maize (Zea mays L.) inbred lines - Adebayo, M.A.; Menkir, A.; Hearne, S.; Kolawole, A.O. (Springer, 2017)
The quest for precise and rapid phenotyping of germplasm is increasing the interest of breeders and physiologists in the application of remote sensing techniques in maize breeding. Twenty-four drought-tolerant maize inbred lines were crossed using a modified North Carolina II mating scheme to generate 96 single-cross hybrids. The parents and the hybrids were evaluated under full irrigation and drought stress conditions in the dry seasons of 2010 and 2011 at Ikenne, southwest Nigeria. Normalized difference vegetation index (NDVI) was recorded at 3- and 8-leaf growth stages. Hybrids differed significantly for NDVI. Both general (GCA) and specific (SCA) combining ability effects were significant for NDVI measured at 8-leaf stage under both irrigation regimes, with GCA accounting for 53% of the total variation under full irrigation. Both additive and non-additive genetic effects played significant roles in the inheritance of NDVI. The females GCA effects for grain yield was positively correlated with females GCA effects for NDVI (r = 0.72, p < 0.0001) and the male GCA effects for grain yield was also correlated with males GCA effects for NDVI (r = 0.78, p < 0.0001) at 8-leaf stage under full irrigation. These results indicate that live green biomass accumulation in maize could be identified through early screening of a large number of genotypes using NDVI for developing productive hybrids.